Dorothy Sherman Severin, Memory in "La Celestina". Tamesis Books, London, 1970; x + 73 pp. / Adrienne Schizzano Mandel, "La Celestina" studies: A thematic survey and bibliography, 1824-1970. Scarecrow, Metuchen, N. J., 1971; 261 pp. / Fernando de Rojas, Celestine or the tragick-comedie of Calisto and Melibea. Trans. by James Mabbe. Ed. by Guadalupe Martínez Lacalle. Tamesis Books, London, 1972; xiii + 268 pp. / Gaspar Gómez de Toledo, Tercera parte de la Tragicomedia de Celestina. Critical ed., introd. and notes by M. E. Barrick. University of Pennsylvania Press, Philadelphia, 1973; x + 597 pp. / Pierre Heugas, "La Célestine" et sa descendance directe. Inst. d'Études Ibériques et Ibero-Américaines de l'Université, Bordeaux, 1973; 612 pp. - Eisenberg, Daniel (El Colegio de México, 1976)
Se reseñaron los libros: Memory in "La Celestina"; "La Celestina" studies: A thematic survey and bibliography, 1824-1970; Fernando de Rojas, Celestine or the tragick-comedie of Calisto and Melibea. Trans. by James Mabbe. Ed. by Guadalupe Martínez Lacalle; Gaspar Gómez de Toledo, Tercera parte de la Tragicomedia de Celestina. Critical ed., introd. and notes by M. E. Barrick; y "La Célestine" et sa descendance directe.